2021
DOI: 10.1155/2021/9495126
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Nanotechnology-Based Strategies for Prevention, Diagnosis, and Treatment of Coronavirus Infections

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is exponentially spreading across the world, leading to an outbreak of serious viral pneumonia. Antiviral therapies using chloroquine, hydroxychloroquine, and favipiravir have been approved by several countries to increase the quality of life of SARS-CoV-2-infected patients. Currently, several companies are intensively working on the production of coronavirus (CoV) vaccines, resulting in some specific vaccines that have been approved for CoV infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 132 publications
0
26
0
Order By: Relevance
“…In this context, understanding nanomaterial interactions with the immune system facilitates the development of specific strategies for immunotherapies. 19 , 55 …”
Section: Nanotubes Mechanisms To Activate Immune Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…In this context, understanding nanomaterial interactions with the immune system facilitates the development of specific strategies for immunotherapies. 19 , 55 …”
Section: Nanotubes Mechanisms To Activate Immune Systemmentioning
confidence: 99%
“… 132 The use of CNTs in the development of nanovaccines represents the “holy grail” in the battle against different diseases, including infections with viruses such as HIV and SARS-CoV-2. 26 , 29 , 55 Therefore, investigating CNT applications related to the immune system is essential to guide the development of nanovaccine research. 106 …”
Section: Perspectives On Vaccine Adjuvants and Carbon Nanotubes Usementioning
confidence: 99%
See 2 more Smart Citations
“…International Journal of Nanomedicine 2021:16 5726 fighting SARS-CoV-2 empirically. 45,[150][151][152] Adeleye et al, identified 15 potential ethnomedicinal herbs from different African countries for the discovery and development of therapeutic agents for COVID-19 applications. 153 Phytotherapeutics has been recognized for its better therapeutics with fewer adverse effects than modern medicines.…”
Section: Dovepressmentioning
confidence: 99%